1989
DOI: 10.1128/jb.171.9.5232-5236.1989
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of the structural gene for alkaline elastase YaB, a new subtilisin produced by an alkalophilic Bacillus strain

Abstract: Alkaline elastase YaB is an extracellular serine protease of the alkalophilic Bacillus strain YaB. We cloned the structural gene, ale, and determined the nucleotide sequence. The mature enzyme (268 amino acids) was preceded by a putative signal sequence and a prosequence (27 and 83 amino acids, respectively). The mature enzyme was 55 % homologous to subtilisin BPN'. Almost all the positively charged residues are predicted to be on the surface of the molecule, which would facilitate binding to elastin. The P1 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
39
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 27 publications
1
39
0
Order By: Relevance
“…The roles of preand propeptides of subtilisin trafficking in bacteria have been studied by biochemical and molecular biological investigations. The prepeptide functions as the signal sequence required for protein secretion across the cytoplasmic membrane, and the propeptide has been proposed to function as an intramolecular chaperone for production of active subtilisin (1,7,22,26). The role of pre-or propeptide in the protozoan subtilases was analyzed in PfSUB-1 (21).…”
Section: Resultsmentioning
confidence: 99%
“…The roles of preand propeptides of subtilisin trafficking in bacteria have been studied by biochemical and molecular biological investigations. The prepeptide functions as the signal sequence required for protein secretion across the cytoplasmic membrane, and the propeptide has been proposed to function as an intramolecular chaperone for production of active subtilisin (1,7,22,26). The role of pre-or propeptide in the protozoan subtilases was analyzed in PfSUB-1 (21).…”
Section: Resultsmentioning
confidence: 99%
“…DY, subtilisin DY (Betzel et al, 1993); SUBT. BPN', subtilisin BPN' (Pantoliano et al, 1989); ISP-I, ISP-1 (Rufo et al, 1990); B. ALCALOPHILUS, subtilisin from Bacillus alcalophilus (van der Laan et al, 1992); ELASTASE YAB, elastase YaB (Kaneko et al, 1989); BSUB MINOR PROT., minor protease from B. subtilis (Sloma et al, 1991); Aqualysin I, aqualysin I from Thermus aquaticus (Terada et al, 1990); PROTEINASE K, proteinase K from Tritirachium album (Gunkel & Gassen, 1989); Predictprotein, secondary structure prediction of Predictprotein algorithm for aerolysin; Thermitase 2", Proteinase K 2", Carlsberg 2", BPN' 2", secondary structures of thermitase, proteinase K, subtilisin Carlsberg, and subtilisin BPN'. a Numbering is based on the first amino acid in the P. aerophilum aerolysin sequence alignment, rather than the position of the initiator methionine.…”
Section: Phvsgalaliksyeeesfqrk--lsesevfaqlirrtlpldiakmentioning
confidence: 99%
“…It was pointed out that Gly166 formed the bottom of P 1 pocket of subtilisin BPN'. 2 7) On the basis of this finding, Kaneko et al 7 ) suggested that the deletion of four amino acids at the region between 161 and 164 might change the conformation of P 1 pocket and deduced that this distortion correlated with the P 1 preference of YaB elastase for Ala, in contrast to that of subtilisin BPN' for Tyr. Since 221 protease, which shared the same deletion, also had high elastolytic activity28,29) and similar cleavage pattern on oxidized insulin B-chain,30) this conformational change of the P 1 pocket might also happen in this protease.…”
mentioning
confidence: 99%
“…amylosacchariticus 6 ) have been cloned and sequenced. Recently, the genes encoding alkaline serine proteases from alkaliphilic Bacillus strains YaB 7 ) and PB92 8 ) have also been cloned and sequenced. Nucleotide and amino acid sequences of these subtilisin-type enzymes share significant homology although these enzymes are distinct from each other in their enzymatic and physicochemical properties.…”
mentioning
confidence: 99%